ANALYZING WULING CONSUMER PURCHASE DECISION AT PT. KUMALA CEMERLANG ABADI (WULING MOTORS) MALALAYANG MANADO. - Vycency T. Runtu; James D.D. Massie; Merinda H.C. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This study aims to analyze the effect of product, promotion, price and location on purchase decision for Wuling cars at PT. Kumala Cemerlang Abadi Manado. The research method used is a qualitative method, with interviews with several consumers for data collection. The target population in this study are consumers who buy Wuling cars at PT. Kumala Cemerlang Abadi. The number of samples used in this study were 10 informants. The results of this study indicate that product quality, price, promotion, and place have a very positive effect on purchasing decisions. This shows that the better the quality of the product, the more attractive the price and promotion, as well as the convenient location, the more influence the purchase decision will have.